Спонукальні конструкції як одна із структурно-семантичних і функціональних особливостей текстів церковних проповідей (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with the functional peculiarities of imperative structures as they appear in church sermons, using a synthetic and semantic analysis.